An Industrial systems design study on Allied Concrete Products, Inc. - Biton, Dennis Paul L.; Estrada, Eric D.C.; Lampa, Nelson C.; Liwanag, Kristian E. (Diliman, Quezon City College of Engineering, 2001)
An Industrial Systems Design study was conducted on Commonwealth Plant of Allied Concrete Products, Inc., which manufactures concrete products sold locally in Metro Manila and other nearby provinces. The study included documentation, evaluation and analyses of the facility's present production system, forecasting, strategic capacity planning, aggregate planning, and identification of possible improvement areas along with their corresponding recommendations. In summary the plant's overall supply chain was studied. The process documented was that of the concrete products, classified accordingly to product types - concrete pipes and decorative blocks. All documentation of company systems was analyzed for the purpose of evaluation. Analyses of the current system resulted in the identification of following problem areas: 91) lack of forecasting; (2) lack of performance evaluation; and (3) inappropriate waging system. To address the problem areas, the implementation of the following recommendations were presented (1) Forecasting of Market Demand ? focusing on the importance and recognition of the contribution Key Performance Indices (KPI's) ? characterized by standardized measurement of performance indices to direct the efforts of the three portions of the supply chain towards the company's overall objective; and (3) Review of Compensation Plan ? emphasizing on waging system highlighted by elimination of unfavorable competition among workers that tends to compromise quality
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Allied Concrete Products, Inc; Marketing channels--Management.; Delivery of goods--Management.; Physical distribution of goods--Management.; Customer services--Management.; Industrial procurement; Materials management; System design